A Systematic Review of Quality of Life Assessments of Offenders - Muller, Ashley Elizabeth (International journal of offender therapy and comparative criminology, 2020)
Strength-based theories of rehabilitation emphasize the importance of opportunities for offenders to achieve “good lives” to not re-offend. The extent to which these groups feel enabled to achieve a good life may be measured through subjective, overall quality of life (QoL). The aim is to systematically review the QoL instruments used among detained offenders and synthesize the factors related to their QoL. A systematic literature review was conducted to retrieve articles that assessed the overall QoL of a sample of detained offenders using a validated instrument. The instruments’ specificity, dimensionality, and respondent and administrator burden were assessed, and factors reported as significantly related to QoL were summarized. In total, 41 articles were included in the review: 20 reported on forensic samples and 20 on prisoners, with one study randomly assigning offenders to either forensic treatment or prison. Among the included articles, 12 validated instruments were utilized. Only one instrument, the Forensic Inpatient Quality of Life Questionnaire, was specifically developed for and validated in forensic patients. Detained offending populations reported lower QoL than the general population, and those with untreated mental illness reported the lowest. The most consistent predictors of QoL longitudinally were social factors, while substance use and detention-specific variables were not consistently related. In general, the relationships between poor mental health, loneliness, and poor QoL seen in offenders are also seen among other marginalized populations. To improve the evidence base for QoL assessment in this vulnerable group, current gold standard QoL instruments should be validated in detained populations.